Are we doing enough? Improved breastfeeding practices at 14 weeks but challenges of non-initiation and early cessation of breastfeeding remain: findings of two consecutive cross-sectional surveys in KwaZulu-Natal, South Africa - C. Horwood; L. Haskins; I. Engebretsen; C. Connolly; A. Coutsoudis; L. Spies (BMC, 2020)
Abstract Background KwaZulu-Natal (KZN) Initiative for breastfeeding support (KIBS) was a multipronged intervention to support the initiation and sustaining of breastfeeding, implemented between 2014 and 2017. We present results of two surveys conducted before and after KIBS implementation to assess changes in infant feeding practices in KZN over this time period. Methods Two cross-sectional surveys were conducted in primary health care clinics. Multistage stratified random sampling was used to select clinics and participants. Sample size was calculated to provide district estimates of 14-week exclusive breastfeeding (EBF) rates at baseline (KIBS1), and provincial estimates at endpoint (KIBS2). At KIBS1 the sample required was nine participating clinics in each of 11 districts (99 clinics) with 369 participants per district (N = 4059), and at KIBS2 was 30 clinics in KZN with 30 participants per clinic (N = 900). All caregivers aged ≥15 years attending the clinic with infants aged 13- < 16 weeks were eligible to participate. Data was collected using structured interviews on android devices. Multi-variable logistic regression was used to adjust odds ratios for differences between time points. Results At KIBS1 (May2014- March2015), 4172 interviews were conducted with carers, of whom 3659 (87.6%) were mothers. At KIBS2 (January-August 2017), 929 interviews were conducted which included 788 (84.8%) mothers. Among all carers the proportion exclusively breastfeeding was 44.6 and 50.5% (p = 0.1) at KIBS1 and KIBS2 respectively, but greater improvements in EBF were shown among mothers (49.9 vs 59.1: p = 0.02). There were reductions in mixed breastfeeding among all infants (23.2% vs 16.3%; p = 0.016). Although there was no change in the proportion of carers who reported not breastfeeding (31.9% vs 32.8%; p = 0.2), the duration of breastfeeding among mothers who had stopped breastfeeding was longer at KIBS2 compared to KIBS1 (p = 0.0015). Mothers who had returned to work or school were less likely to be breastfeeding (adjusted odds ratio [AOR] 3.76; 95% CI 3.1-4.6), as were HIV positive mothers (AOR 2.1; 95% CI 1.7-2.6). Conclusion Despite improvements to exclusive breastfeeding, failure to initiate and sustain breastfeeding is a challenge to achieving optimal breastfeeding practices. Interventions are required to address these challenges and support breastfeeding particularly among working mothers and HIV positive mothers.